2011
DOI: 10.1074/jbc.m111.274779
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modifiers of Cardiovascular Phenotype Caused by Elastin Haploinsufficiency Act by Extrinsic Noncomplementation

Abstract: Background: Variability in vascular pathology is associated with elastin loss-of-function mutations. Results: Quantitative trait loci and several candidate genes that modify vessel pathology were identified in a mouse model of elastin insufficiency. Conclusion: The effects of elastin insufficiency are determined by interactions between the primary elastin defect and unrelated secondary modifiers. Significance: Identification of modifier genes enhances our understanding of disease mechanisms associated with ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…Williams-Beuren Syndrome (WBS) is a developmental disorder that is marked by arterial defects leading to hypertension. Deletion of one of the two functional copies of NCF1 protects a subset of WBS patients against hypertension, a finding that was recapitulated in a mouse model of the disease using the NOX inhibitor apocynin (37,146). However, in another study of two patients with WBS and CGD who lacked any functional NCF1 gene, there was no protection against hypertension, suggesting that factors other (or in addition to) than NOX in vascular tissue may be involved in hypertension (281).…”
Section: Human Disease Associations With Polymorphisms In Nox2 and Phmentioning
confidence: 99%
“…Williams-Beuren Syndrome (WBS) is a developmental disorder that is marked by arterial defects leading to hypertension. Deletion of one of the two functional copies of NCF1 protects a subset of WBS patients against hypertension, a finding that was recapitulated in a mouse model of the disease using the NOX inhibitor apocynin (37,146). However, in another study of two patients with WBS and CGD who lacked any functional NCF1 gene, there was no protection against hypertension, suggesting that factors other (or in addition to) than NOX in vascular tissue may be involved in hypertension (281).…”
Section: Human Disease Associations With Polymorphisms In Nox2 and Phmentioning
confidence: 99%
“…A similar strategy was used in mice heterozygous for a null elastin allele ( Eln +/− ) (Kozel et al 2011). In humans, the ELN gene resides within the microdeletion associated with Williams syndrome.…”
Section: Modifier Genesmentioning
confidence: 99%
“…Although it is now well established that ELN loss or mutation is the primary driver of the vascular lesions in these genetic syndromes, there are likely multiple modifiers that contribute to the phenotype variation. A recent study using quantitative trait locus analysis in mice identified several potential genetic modifiers of the ELN deficiency vascular phenotype, including genes involved in reactive oxygen species generation (Kozel et al, 2011). We and others have identified several additional factors that can modify ELN expression at transcriptional and posttranscriptional levels, including specific miRNA species, growth factors, and control of the cell cycle (Kuang and Goldstein, 2003;Sen et al, 2011;Shi et al, 2012;Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 83%